Epic Poetry and the Origins of Evolutionary Theory - Holmes, John (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2016)
In this article I will examine how Erasmus and Charles Darwin responded to the epic tradition in their writings, and how the legacy of epic was worked into their respective evolutionary visions. Erasmus Darwin formulated a brief sketch of his evolutionary theory in prose in his medical textbook Zoonomia, but when he came to flesh out his conception of evolution in imaginative and empirical detail he turned to verse. His poem The Temple of Nature, published posthumously in 1803, self-consciously evokes epic conventions and engages intertextually with Milton, Lucretius and Ovid in particular. One of the poems that Erasmus Darwin replied to in his verse – Paradise Lost – was by Charles Darwin’s account his constant companion during his voyage on the Beagle. Through exploring how both Darwins responded to Milton’s vision of Creation, and to the counter-visions offered by other epic poets and by Satan within Milton’s own poem, it is possible to see how fundamental epic poetry was to the generation of evolutionary theory and the forms it came to take.